Nathan B. answered • 03/05/18

Tutor

5
(20)
Elementary and Algebraic skilled

2x

^{2}- 25x = 3x^{2}- 8x - 6What we need to do is move all the pieces to one side of the equals sign, so that the problem equals 0. So we subtract 2x2 and add 25x to both sides:

0 = x

^{2}+ 17x - 6This doesn't look like it will factor out evenly, so let's use the quadratic formula:

(-b ± √(b

^{2}- 4ac)) / 2ax = (-17 ± √(17

^{2}- 4 * 1 * -6)) / (2 * 1)x = (-17 ± √(289 + 24)) / 2

x = (-17 ± √313) / 2

x = (-17 + √313) / 2, or (-17 - √313) / 2

The problem is that square root 313. That's as far as we can go if we want to be completely accurate. Otherwise we're going to have to round off that root:

x ≅ (-17 + 17.691) / 2, or (-17 - 17.691) / 2

x ≅

^{0.691}/_{2}, or -^{34.691}/_{2}x ≅ 0.3455 or -17.3455

Robert A.

03/05/18